Endothelin B receptor deficiency is associated with an increased rate of neuronal apoptosis in the dentate gyrus - Ehrenreich, Hannelore; Nau, R.; Dembowski, C.; Hasselblatt, M.; Barth, Martin; Hahn, A.; Schilling, Lothar; Sirén, A. -L.; Brück, W. (Neuroscience, 1999)
The dentate gyrus retains neuronal proliferative potential throughout life. Using immature endothelin B receptor-deficient (sl/sl) rats, a rabbit model of pneumococcal meningitis and autopsy brains from humans who died from pneumococcal meningitis, we explored the role of endothelin B receptors in physiological and pathological neuronal apoptosis in the dentate gyrus. At postnatal days 3-4, the rate of apoptosis in the dentate gyrus was high in all rats, declining to low levels in wild-type rats (+/+) on days 14 and 22, but remaining high in both homozygous (sl/sl) and heterozygous (sl/+) endothelin B receptor-deficient rats. Increased apoptosis was not significantly compensated for by neuronal proliferation. Hippocampal neuronal cultures also exhibited genotype-dependent apoptosis with the highest rate in neurons from homozygous endothelin B receptor-deficient (sl/sl) rats. In rabbit and human pneumococcal meningitis, increased apoptosis in the dentate gyrus was associated with loss of neuronal endothelin B receptor immunoreactivity. In conclusion, endothelin B receptors appear to act as neuronal survival factors in the dentate gyrus in rodents and man, both during postnatal development and under pathological conditions.